The Role of the Community in the Population of the Javanese Eagle (Nisaetus bar-telsi) in the Mount Picis Ponorogo Nature Reserve Area - Lina Yuliamalia; Sunarto; Trisni Utami (Nusantara Science and Technology Proceedings)
Society is a group of people who interact with each other, in scientific terms is interacting with each other. A human unit can have infrastructure through which its citizens can interact with each other. The role of the community is very important because it can obtain information about environmental conditions, needs, and real community attitudes. One of the endemic birds of prey found in Indonesia is the Javanese Eagle (Nisaetus bartelsi). The Javan Eagle population is increasingly threatened with extinction due to illegal trade, poaching, and land constriction. The Nature Reserve of Mount Picis is a place for flora and fauna to live, grow, and develop well, including the Javanese Eagle. The purpose of this study was to determine the role of the community towards the Javanese eagle population in the area of ??Mount Picis Ponorogo Nature Reserve. This method is a descriptive study using qualitative research methods. The results of the study explained that the community realized that the area was a protection for sloping land, a storage for water, air, plants and animals that provided benefits to the people around the area. Efforts made to increase community active participation in preserving the area are community empowerment, through various assistance provided by the government. In 2013 and 2014, there were 3 Javanese eagles, consisting of 2 adults and 1 teenager. In 2015, the observation team found 1 Javanese eagle family consisting of 2 adults and 1 teenager. In 2016, 1 young Javanese eagle was released. In 2017, the observation team found 1 adult Javanese eagle. In 2018 who found 1 adult Javanese eagle, and in other locations found 1 young Javanese eagle and 1 adult Javanese eagle. Then in 2019, 1 adult Javanese eagle was released, so it is known that the estimated population of Javanese eagles in this conservation area is 3-4 individuals. The results of the study explain that the role of the community is very important for the survival of the Javanese eagle in the Mount Picis Nature Reserve area. This is evidenced by the cooperation between area guard officers (government) and the community around the area. Together, they maintain and preserve the flora and fauna so that the balance of the ecosystem is maintained properly. Key words: nature reserves; Javanese Eagle; Public; population